Relationships Between Personality and Work Environment Type and Work Stress Symptoms in Students of Dental Profession Education - Primasari, D. N.; Hariyani, N.; Ramadhani, A. (International Journal of Psychosocial Rehabilitation, 2020)
Background: Stress is the body’s response to represent discomfort due to various environmental factors. The stress experienced by dentists begins when they take dentistry education. The prevalence of stress reaches 89.7% in dentists in Malaysia. Personality type and work environment are important factors for identifying and approaching stress symptoms. Big five frameworks (Openness, Conscientiousness, Extraversion, Agreeableness, Neuroticism) are models that are often used to describe individual personalities. Objective: To determine the relationship between personality and work environment types and work stress symptoms in students of the dental profession education Faculty of Dentistry, Institute of Health Sciences Bhakti Wiyata Kediri. Method: This type of study was cross-sectional. The sampling technique used a simple random sampling technique with a sample size of 120 people.’ Results: Data analysis used One Way Anova test found a significant relationship between personality types and work stress symptoms (P = 0.001) with Neuroticismism as the strongest predictor of work stress symptoms. The results of Pearson correlation test analysis found a significant relationship between work environment and symptoms of work stress (P = 0.000). Conclusion: There is a relationship between personality and work environment type and the work stress symptoms in students of the dental profession education Faculty of Dentistry, Institute of Health Sciences Bhakti Wiyata Kediri.